Relationship between Communication, Quality of Service and Quality of relationship on Voluntary Performance (Study at Conventional Travel Agency PT. Garuda Indonesia (Persero), Tbk Semarang Branch Office) - Indri Apriani Rahma Pratama; Mahfudz Mahfudz (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The travel agency industry has now entered a new chapter. Since the development and proliferation of online travel agencies (OTAs) the market share of conventional travel agencies has been eroded.  Even so, this happened the other way around in conventional travel agencies partnering with PT Garuda Indonesia Semarang Branch Office. The strategy of developing relationships in the supply chain is alleged to be able to improve the performance of companies and partners. Therefore, this case study research was conducted to analyze the effect of service quality and communication on the quality of supply chain relationships and their implications for voluntary performance at PT Garuda Indonesia Semarang Branch Office. As a result, there is a significant positive relationship for communication variables to voluntary performance and service quality to relationship quality.